PEDAGOGICAL MONITORING AS EFFECTIVE TOOL OF DIAGNOSIS OF STUDENT DEVELOPMENT IN THE SYSTEM PERSONALITY-ORIENTED LEARNING (Pedagogy of Higher and Secondary Education, 2008)
In article pedagogical monitoring as the tool of diagnostics of development of pupils, and also the basic pedagogical conditions of his effective using in system of personality-oriented teaching are considered.